Decrease of frequency of conversions of short-scar incision to the aorta using pre-operative 3D-modeling on the basis of the changes in aorta and patient's individuality - A. M. Putintsev; R. V. Sultanov; V. A. Lutsenko; S. V. Moshneguts (Acta Biomedica Scientifica, 2015)
The increase of the number of patients with atherosclerosis of the aorta leads to steady growth of the number of operations on aorta-femoral segment. In this regard, Federal programs of Federal funding are created for treatment of this disease. However, a high rate of mortality in cases of standard operations causes surgeons to minimize the volume of surgical treatment. The method of operation of the aorta from short-scar incision is studied quite enough; however, there are some problems, such as incision conversion and intraoperative complications. The aim of this study is to improve the results of operations on the aorta from the short-scar incision by access modeling. We analyzed the results of treatment of 88 patients operated from short-scar incision to the aorta in the Kemerovo Regional Clinical Hospital. Patients were divided into two groups - 55 patients operated without access modeling and 33 patients operated with preoperative access modeling. In the result in the second group there was reduction of incision conversions frequency to 3,03%, also there was reduction of the operation time in comparison with the first group without access modeling, with comparable characteristics of the groups and of the same frequency and nature of complications.